Beyond Documentary: Blazing Trails Between Romanticism and Realism in American War Novel - Suk, Jan (American & British Studies Annual, 2017)
Review of Jozef Pecina, The Representation of War in Nineteenth-Century American Novels. Trnava: Univerzita sv. Cyrila a Metoda v Trnave, 2015. 116 p. ISBN 978–80–8105–731–1